Finding the shortest path using the ant colony optimization - Yella Swamy, K; Gogineni, Saranya; Gunturu, Yaswanth; Gudapati, Deepchand; Tirumalasetti, Ramu (International Journal of Engineering and Technology, 2017)
An ant colony optimization(ACO) is a techniquewhich is recently introduced ,and it is applied to solve several np-hard problems ,we can get optimal solution in a short time Main concept of the ACO is based on the behavior of ants in their colony for finding a source of food. They will communicate indirectly through pheromone trails. Computer based simulation is can generate good solution by using artificial ants, by using that general behavior we are solving travelling Sale man problem.
Keywords: Optimization; Quadratic; Pheromone; Trails; NP-Hard.